THE EFFECTS OF CIVIL WAR ON DEVELOPMENT IN SOUTH SUDAN - Dario, Joseph Lual; Alier, Dr. Gabriel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This argument entitled “The Effects of civil war on development in south Sudan”: from (1955-2005) has been chosen because it reflects the attempted secession by a region that is territorially contiguous with the area around the state.The civil war was a conflict between northern Sudan and the southern Sudan region that demanded representation and regional autonomy, the war resulted in the independence of south Sudan six years after the war ended.   The observations were that, there were similarities in most of the other countries where civil war has occurred (USA, India, Mali, Ethiopia among others.  The data was accessed through survey questionnaires and has been able to accessed 100 respondents in Wau municipality.  However after accessing the data from the field, the findings were that the main attributes effect of civil war on development in south Sudan was the low level of development and there were lack of peace and reconciliation. Based on the findings, it has been able to offer recommendations such as Army should refrain from political affairs, avoiding Politian’s willpower as a follower and should fulfill the needs of citizen by protecting their properties and life’s. And defending the country, allowed civilian to exercise democracy rightly with focus on developmental activities. Then government should Strategies on the issues related to good governance and power must be in the hand of citizen not politician. Finally, these results of this study resolve greatly assist people of South Sudan in averting future civil war.